Design of Tracking System for Kids - Shamuri, Muhammad NorHasib; Alias, Rozlan (Evolution in Electrical and Electronic Engineering, 2021)
Recently many cases of missing children have been reported. Parents are always worried about the possibility of their children being abducted. Therefore, the purpose of this paper is to develop a wearable tool that can be used to track a missing child within a certain distance based on the Internet of Things (IoT) to overcome the problem. This technology can be very useful in the field of security. The project focuses on the development of a wearable GPS-based system and a Blynk app for tracking children. This will help parents find their child easily. In addition, the system will allow users to track children remotely over a mobile network. This will also allow the user to get the coordinates of the latitude and longitude and the whereabouts of the child. The system consists of two main components: a NEO6M GPS receiver and a NodeMCU module. The latter has a built-in GPS receiver that allows tracking of children.